Transitions between nonlinear regimes in melting and liquid bridges in microgravity. (1st September 2022) - S̆eta, B.; Dubert, D.; Prats, M.; Gavalda, Jna.; Massons, J.; Bou-Ali, M.M.; Ruiz, X.; Shevtsova, V.
Highlights: Non-linear dynamics of melting (MB) and liquid (LB) bridges are compared. The azimuthal wavenumbers of LB and fully melted MB are different at small Δ T . The frequency of fully melted MB is lower than of LB. The MB and LB frequencies coincide when flow patterns are similar for the same amount of liquid fraction. Higher embedded dimension number of MB than LB points a higher complexity of the flow. Graphical abstract: Abstract: Phase change materials (PCM) are commonly used for energy storage in a variety of terrestrial applications and offer promise for future space exploration. We present a three-dimensional numerical investigation of the thermocapillary (Marangoni) flows in liquid and melting bridges in microgravity. The focus is placed not only on the role of the melting process in changing flow regimes, but also on emphasizing comparative nonlinear dynamics in these bridges. The hydrothermal instability in a melting bridge (MB) with a unit aspect ratio is compared to the liquid bridges with an aspect ratio between 0.7 and 1, in order to match the liquid fraction during the melting process with the liquid content in the liquid bridge. Since the characteristic size affects the Marangoni number, the temperature difference between the disks ( Δ T ) is selected as the control parameter, and calculations are carried out for Δ T = 25, 30, 40 K. At the end of the melting process, an oscillatory traveling wave regime is established in both systems at high Δ T, albeit with different frequencies. At low Δ T, this similarity disappears. The processing of temperature time-series, such as the density power spectrum (PSD), the spectral entropy (SEN) and the embedded dimension, was used to describe and compare flow patterns in liquid and melting bridges.